Key challenges in the advancement and industrialization of biobased and biodegradable plastics: a value chain overarching perspective - Börner, Tim; Zinn, Manfred (Frontiers in Bioengineering and Biotechnology, 2024)
At the International Symposium on Biodegradable Polymers (ISBP2022) in Sion, Switzerland, experts from academia and industry underscored the remarkable progress in biobased and biodegradable polymers (BBPs) since their initial commercialization around 50 years ago. Despite significant advancements, the technology readiness level (TRL), market adoption, and industrialization of BBPs is not yet competitive to conventional plastics. In this perspective, we summarize the challenges and requirements for advancing the development and industrialization of BBPs, drawing insights from international experts coming from academia and industry, who had participated in the survey and podium discussion during the ISBP2022. In fact, BBPs grapple with persistent and emerging challenges throughout the value chain. These challenges can be grouped into four areas and involve i) the pursuit of sustainable feedstocks together with efficient production and downstream processes as well as recycling technologies and infrastructure; ii) meeting or revisiting product requirements by industry, markets, and consumers; iii) navigating a non-level playing field in their sustainability assessment (LCA) compared to conventional plastics; and iv) struggling with underdeveloped and partially biased policy and financial frameworks as well as lacking clear definitions, terminologies and communication.